GAMBARAN SANITASI DASAR RUMAH DAN PERSONAL HYGIENE PADA PENDERITA TB DI WILAYAH KERJA PUSKESMAS DRIYOREJO KABUPATEN GRESIK - Yeti Kurniatiningsih; Fitri Rokhmalia; Suprijandani (Poltekkes Kemenkes Surabaya, 2022)
Tuberculosis is one of the environmental-based diseases. Home sanitation and personal hygiene factors can affect the transmission of disease. According to data from the Driyorejo Health Center in 2020 the number of people suffering from tuberculosis from January to September was 71 people. The purpose of this study was to describe the condition of basic home sanitation and personal hygiene for TB patients in the working area of ​​the Driyorejo Health Center, Gresik. This type of research uses descriptive research with a qualitative approach. The samples used were 42 houses with TB patients. Data collection was done by observation and interviews. Analysis of the data used is descriptive analysis in the form of tables and narratives. The results of the study on basic sanitation of TB patients' houses that did not meet the requirements in the work area of ​​the Driyorejo Health Center temperature of 33 houses (79%), humidity of 32 houses (76%), lighting of 27 houses (64%), and ventilation of 25 houses (60%). The type of floor that meets the requirements is 39 houses (93%) (Personal hygiene of patients who are not good 9 people (21%) and 28 people (67%). The conclusion of the study of TB patients' homes in the working area of ​​the Driyorejo Health Center was 64% who did not meet the requirements. Personal hygiene more than 50% have done quite well. To prevent disease transmission, it is hoped that the community will improve the sanitation conditions of the house and further improve personal hygiene and clean and healthy living behavior.